Comparative value of full-fat corn germ, whole cottonseed and tallow as energy sources for lactating dairy cows - W.F. Miller; Evan C. Titgemeyer; Michael V. Scheffel; R.T. Ethington (Kansas Agricultural Experiment Station Research Reports, 2002)
We used 24 multiparous Holstein cows in 4 x 4 Latin square design to evaluate full-fat corn germ as a replacement for whole cottonseed and tallow in total mixed diets for lactating dairy cows. Experimental diets on a dry matter basis were: 1) control 3.5% fat; 2) whole cottonseed 5.1% fat; 3) tallow 5.1% fat; 4) full-fat corn germ 5.1% fat. Diets were fed as total mixed rations typical of that fed on commercial dairy operations. Cottonseed meal and cottonseed hulls were included in the control, tallow, and full-fat corn germ diets to balance for fiber and protein fractions equal to those in the whole cottonseed diet. Dry matter intake, milk production, and energy corrected milk did not differ among the diets. Milk from cows fed full-fat corn germ contained less fat than milk from cows fed whole cottonseed but was similar to that of milk from cows fed control or tallow diets. Milk protein percentage was lower for cows fed full-fat corn germ than those fed control, but similar to cows fed whole cottonseed or tallow. Percentage milk lactose did not differ among dietary treatments. Cows fed WCS produced more pounds of milk fat than cows fed full-fat corn germ or tallow, but protein and lactose yield did not differ among the diets. Cows fed whole cottonseed produced milk more efficiently than cows fed control, tallow, or full-fat corn germ. Unexpectedly, efficiency of energy corrected milk production was not improved by tallow and tallow did not depress dry matter intake. Somatic cell count did not differ among experimental diets. Urea nitrogen concentration was lower in milk from cows fed full-fat corn germ and tallow than those fed whole cottonseed. All diets led to gains in body weight. The handling and storage characteristics of full-fat corn germ enhances its desirability as a feedstuff for dairy cattle. Full-fat corn germ supported milk production as well as whole cottonseed but not milk fat percentage or fat yield at the level fed in our diets. Additional studies need to be conducted to determine the most advantageous amount to feed full-fat corn germ and clarify the mechanisms by which it depresses milk fat production.; Dairy Day, 2002, Kansas State University, Manhattan, KS, 2002;
Keywords: Dairy Day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-121-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 898; Dairy; Energy; Full-fat corn; Tallow; Cottonseed; Cows